2012
DOI: 10.1152/ajpcell.00207.2012
|View full text |Cite
|
Sign up to set email alerts
|

Satellite cell depletion does not inhibit adult skeletal muscle regrowth following unloading-induced atrophy

Abstract: Resident muscle stem cells, known as satellite cells, are thought to be the main mediators of skeletal muscle plasticity. Satellite cells are activated, replicate, and fuse into existing muscle fibers in response to both muscle injury and mechanical load. It is generally well-accepted that satellite cells participate in postnatal growth, hypertrophy, and muscle regeneration following injury; however, their role in muscle regrowth following an atrophic stimulus remains equivocal. The current study employed a ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
115
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(130 citation statements)
references
References 31 publications
(48 reference statements)
9
115
1
3
Order By: Relevance
“…These findings raise the question of whether satellite cells are necessary for muscle hypertrophy, at least the amount that is generally elicited with exercise-training paradigms used for health and wellness of older individuals and the treatment of sarcopenia. This general question has been debated recently (63,76), and the answer is apparently not yet at hand (46,60,83).…”
mentioning
confidence: 99%
“…These findings raise the question of whether satellite cells are necessary for muscle hypertrophy, at least the amount that is generally elicited with exercise-training paradigms used for health and wellness of older individuals and the treatment of sarcopenia. This general question has been debated recently (63,76), and the answer is apparently not yet at hand (46,60,83).…”
mentioning
confidence: 99%
“…The effect of satellite cell ablation on skeletal muscle regrowth following atrophy was also reported 15) . Adult tamoxifen-inducible Pax7-DTA mice were subjected to either 2 weeks of hindlimb suspension to induce muscular atrophy or 2 weeks of hindlimb suspension followed by 2 weeks of reloading to allow regrowth.…”
Section: Role Of Satellite Cells In Muscular Hypertrophy and Regrowthmentioning
confidence: 95%
“…However, Jackson et al (18) reported that myonuclear number in transgenic Pax7-DTA mice with depletion of satellite cells (Ͼ90%) following administration of tamoxifen did not change in response to hind limb unloading and reloading, but atrophy and regrowth of soleus were induced following 14 days of unloading and reloading. Therefore, muscle atrophy caused by hind limb unloading may be recovered because the basal myonuclear number was maintained.…”
Section: Responses To Reloadingmentioning
confidence: 99%
“…The same group as Jackson et al (18) studied the responses of muscle fiber size to functional overloading in transgenic Pax7-DTA mice with depletion of satellite cells following administration of tamoxifen (15,29). In response to 2-wk overloading, hypertrophy was induced in plantaris, although myonuclear number did not change (29).…”
Section: Responses To Reloadingmentioning
confidence: 99%
See 1 more Smart Citation